Exploring the Y-Balance-Test scores and inter-limb asymmetry in soccer players: differences between competitive level and field positions - González-Fernández, F. T.; Martínez-Aranda, L. M.; Falces-Prieto, M.; Nobari, H.; Clemente, F. M. (BMC Sports Science, Medicine and Rehabilitation, 2022)
Background The postural stability seems to be important in the physical development of the soccer player and the specific tasks related to the game. In addition, it is related to the injury risk and therefore, with the injury prevention and retraining processes. In this context, the Y Balance Test (YBT) is presented as a tool to assess dynamic postural control.